An Adaptation of the Original Fresno Test to Measure Evidence‐Based Practice Competence in Pediatric Bedside Nurses. Issue 3 (5th May 2018) - Laibhen‐Parkes, Natasha; Kimble, Laura P.; Melnyk, Bernadette Mazurek; Sudia, Tanya; Codone, Susan
ABSTRACT: Purpose: Instruments used to assess evidence‐based practice (EBP) competence in nurses have been subjective, unreliable, or invalid. The Fresno test was identified as the only instrument to measure all the steps of EBP with supportive reliability and validity data. However, the items and psychometric properties of the original Fresno test are only relevant to measure EBP with medical residents. Therefore, the purpose of this paper is to describe the development of the adapted Fresno test for pediatric nurses, and provide preliminary validity and reliability data for its use with Bachelor of Science in Nursing–prepared pediatric bedside nurses. Methods: General adaptations were made to the original instrument's case studies, item content, wording, and format to meet the needs of a pediatric nursing sample. The scoring rubric was also modified to complement changes made to the instrument. Content and face validity, and intrarater reliability of the adapted Fresno test were assessed during a mixed‐methods pilot study conducted from October to December 2013 with 29 Bachelor of Science in Nursing–prepared pediatric nurses. Results: Validity data provided evidence for good content and face validity. Intrarater reliability estimates were high. Linking Evidence to Action: The adapted Fresno test presented here appears to be a valid and reliable assessment of EBP competence in Bachelor of Science in Nursing–prepared pediatric nurses. However, further testing of this instrument is warranted using a larger sample of pediatric nurses in diverse settings. This instrument can be a starting point for evaluating the impact of EBP competence on patient outcomes.